PRODUCTION OF ARTIFICIAL COLD FOR INDUSTRY, BASED ON THE MAGNETOCALORIC EFFECT - Dorin, Botoc; Ionut-Bogdan, Rusu; Adrian , Plesca; Jurij, Avsec (Journal of Energy Technology, 2024)
The most common current technology for producing artificial cold is based on the operation of gas compression and absorption, which was discovered more than a century ago. This technology uses refrigerants as a heat transfer agent. Magnetic refrigeration is an innovative technology that works based on the magnetocaloric effect and the properties of certain rare materials/metals. The presentpaper describes a simulation of the magnetocaloric effect (MCE) of a gadolinium plate (Gd.), which is the main component of the active magnetic regenerator (AMR). The first part includes a descriptionand history of the discovery of the magnetocaloric effect of materials that possess such properties. The continuation is a COMSOL Multiphysics modelling of AMR’s main component: a gadolinium (Gd)plate. The simulation of the magnetocaloric effects and the heat dispersion on its surface was done in COMSOL, as was the highlighting of the adiabatic temperature on the flat surface of the plate. Water was used as a heat transfer agent, and gadolinium (Gd) was used as a reference criterion for the materials. The model simulates a single step of the magnetic refrigeration cycle and evaluates the AMR’s performance with a single board. This study enables identifying the most important characteristics that influence the active magnetic regenerator’s thermal behaviour.